Quantifying the influence of long-term overexploitation on deep groundwater resources across Cangzhou in the North China Plain using InSAR measurements - Bai, Lin; Jiang, Liming; Zhao, Yong; Li, Zhenhong; Cao, Guoliang; Zhao, Chaoying; Liu, Rong; Wang, Hansheng (Journal of hydrology (Amsterdam), 2022)
•We estimate the GWS depletion and remaining exploitable GWS in Cangzhou in 1960–2010.•The total exploitable deep GWS in Cangzhou decreased by 49.8%∼52.2% during 1960–2010.•Groundwater overexploitation leads to permanent loss of groundwater storage capacity.•InSAR is an effective tool for assessing sustainability of a confined aquifer system. Deep groundwater (confined groundwater) is the major water source in Cangzhou, situated in the North China Plain. Long-term deep groundwater overexploitation has resulted in substantial groundwater storage (GWS) depletion. Quantifying the influence of long-term overexploitation on deep groundwater resources is extremely important to maintain the sustainability of the confined aquifer system. In this study, we estimate the amount of total exploitable GWS and total GWS depletion during 1960–2010 in the confined aquifer system across Cangzhou by combining use of the InSAR deformation, estimated skeletal storativity, hydraulic head observations, and hydrogeological data. The total exploitable GWS in Cangzhou was 26.1 ± 21.3 km3 and decreased by 13.0 ± 8.1 km3 ∼ 13.6 ± 8.5 km3 until 2010, accounting for 49.8%∼52.2% of the total amount. It is worth noting that 87.4%∼87.9% of the total GWS depletion is irreversible, leading to a substantial permanent loss of groundwater storage capacity. Our results suggest that the long-term overexploitation has threatened the water supply security in Cangzhou. It is demonstrated that InSAR can be an effective tool for assessing the “physical state” and “sustainable development potential” of a confined aquifer system.